2023
DOI: 10.3390/jfmk8010018
|View full text |Cite
|
Sign up to set email alerts
|

The Issue of Gender Bias Represented in Authorship in the Fields of Exercise and Rehabilitation: A 5-Year Research in Indexed Journals

Abstract: Despite progress made in recent decades, gender bias is still present in scientific publication authorship. The underrepresentation of women and overrepresentation of men has already been reported in the medical fields but little is known in the fields of exercise sciences and rehabilitation. This study examines trends in authorship by gender in this field in the last 5 years. All randomized controlled trials published in indexed journals from April 2017 to March 2022 through the widely inclusive Medline datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Among critical care, clinical trials published between 1981 and 2020, 11.8% of the first authors were females [45], while the proportion was 24.6% and 16.6% in the first and last authorship positions among clinical trials published between 2000 and 2022 [46]. Similarly, the proportions of females in the first and last authorship positions were 27.7% and 14.9% among neurovascular clinical trials (2000-2021) [47], 33.3% and 26.4% in rheumatology (2015-2019) [48], 28.4% and 16.8% in sports medicine (2000-2020) [49], 46.6% and 33.4% in exercise/rehabilitation (2014-2022) [50], and 36.2% and 26.9% in dermatology (2010-2020) [51] subdisciplines.…”
Section: Representation Of Female Authors In Clinical Trialsmentioning
confidence: 93%
See 1 more Smart Citation
“…Among critical care, clinical trials published between 1981 and 2020, 11.8% of the first authors were females [45], while the proportion was 24.6% and 16.6% in the first and last authorship positions among clinical trials published between 2000 and 2022 [46]. Similarly, the proportions of females in the first and last authorship positions were 27.7% and 14.9% among neurovascular clinical trials (2000-2021) [47], 33.3% and 26.4% in rheumatology (2015-2019) [48], 28.4% and 16.8% in sports medicine (2000-2020) [49], 46.6% and 33.4% in exercise/rehabilitation (2014-2022) [50], and 36.2% and 26.9% in dermatology (2010-2020) [51] subdisciplines.…”
Section: Representation Of Female Authors In Clinical Trialsmentioning
confidence: 93%
“…Of the included studies, one reported authorship trends in both clinical trials and clinical practice guidelines [39], while more than 15 studies exclusively reported authorship trends in clinical trials [40][41][42][43][44][45][46][47][48][49][50][51][52][53] and 14 reported authorship trends in clinical practice guidelines [54][55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Gender gaps in the representation of female researchers are reported to be narrowing in various academic fields, particularly in the life sciences and medicine [ 17 ]. However, gender disparities in the quantity and quality of publications and the undertaking of research projects still widely exist [ 18 20 ]. Although existing research has examined the relationship between patenting and variables such as gender dominance in certain fields [ 21 ], gender diversity in teams [ 22 ], and gender composition [ 23 ], the gender differences in knowledge transfer and technology commercialization remain understudied.…”
Section: Introductionmentioning
confidence: 99%